The influence of organic-film morphology on the efficient electron transfer at passivated polymer-modified electrodes to which nanoparticles are attached - Barfidokht, A.; Ciampi, S.; Luais, E.; Darwish, Nadim; Gooding, J. (Wiley VCH, 2013)
The impact of polymer-film morphology on the electron-transfer process at electrode/organic insulator/nanomaterial architectures is studied. The experimental data are discussed in the context of the most recent theory modelling the nanoparticle-mediated electron-transfer process at electrode/insulator/nanomaterial architectures proposed by Chazalviel and Allongue [J. Am. Chem. Soc. 2011, 133, 762-764]. A previous report [Anal. Chem. 2013, 85, 1073-1080] by us qualitatively verified the theory and demonstrates a transition from thickness-independent to thickness-dependent electron transfer as the layer thickness exceeds a certain threshold. This follow-up study explores a different polymer, poly(phenylenediamine), and focuses on the effect of the uniformity of organic film on electron transfer at these hybrid structures. Electron-transfer kinetics of modified surfaces, which were assessed using the redox species Ru(NH3)6 3+ in aqueous solution, showed that a thickness-dependent electron-transfer regime is achieved with poly(phenylenediamine). This is attributed to the sufficiently thin films never being fabricated with this polymer. Rather, it is suggested that thin poly(phenylenediamine) layers have a globular structure with poor film homogeneity and pinhole defects. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.